GC-MS Profiling and Therapeutic Potentials of Prosopis juliflora (Sw.) DC: Cytotoxic and Antimicrobial Insights - Asaad Khalid; Eltuhami A. Abdalgadir; Iman K. Abdel Gadir; Ashraf N. Abdalla; Husham E. Homeida; Shahnaz Sultana; Zia ur Rehman; Rym Hassani; Ahmed Shaher Alqahtani; Hassan A. Alhazmi (Journal of Spectroscopy)
Plants belonging to the genus Prosopis L. (family Fabaceae, subfamily Mimosoideae) have gained significant popularity in traditional medicine due to their potential as anticancer, antidiabetic, anti-inflammatory, and antibacterial compounds. The primary objective of this work was to determine the phytochemical composition of the ethanolic extract derived from Prosopis juliflora leaves, as well as to assess its antibacterial and cytotoxic properties. The phytochemical screening using GC-MS revealed the presence of phytosteroids, ketone, esters, diisooctyl phthalate, and triterpenes. Besides, varying amounts of some silicon derivatives, which were reported to have antimicrobial activity, were detected with octasiloxane, which showed the highest amount (18.47%). 6-Ethoxy-6-methyl-2-cyclohexenone (antioxidant, antidiabetic, antiobesity, and antimicrobial) was detected in considerable quantity. Cytotoxic activity was seen in human breast cancer (MCF-7), human ovary adenocarcinoma (A2780), and human colon adenocarcinoma (HT-29) cell lines, as well as in normal human fetal lung fibroblasts (MRC-5), when subjected to the MTT assay. The plant extract exhibited the highest level of activity (5.75 μg/mL) against the A2780 cell line, with the MCF-7 cell line showing a somewhat lower level of activity (18.49 μg/mL). The antibacterial effect of the plant extracts was evaluated against four standard Gram-positive and four standard Gram-negative. The antimicrobial potential was observed only against Staphylococcus aureus which recorded a 14.5 ± 0.05 mm inhibition zone. The present study has demonstrated the identification of bioactive constituents in P. juliflora plant extracts, which exhibit significant cytotoxic activity against breast and colon malignancies. The study also highlighted P. juliflora extract as an antibacterial against S. aureus.